Translating the lectionary: some considerations - O'Loughlin, Thomas (The Society for Liturgical Study, 2015)
In any discussion of lectionaries and the biblical version employed, the focus is on the translation as a function of the biblical text as an entity in itself; the focus should be on the role of the biblical texts in liturgical assemblies. As these vary in purpose, audience, and the way they relate to the biblical periscopes used, so there must be a corresponding range of versions: each intended for specific liturgical situations.